Distribution Optimization in Supply Chain Management Using the Vehicle Routing Problem (VRP): A Case Study of CV. Angga Putra Sejahtera - Hendry Anggraito (Electronic Journal of Education, Social Economics and Technology, 2025)
Distribution is a vital element of Supply Chain Management (SCM) since it influences the operational costs and service level. CV. APS, a company that distributes Nylon 66 and polyester monofilament for kite string artisans in the districts of Bandung, Sumedang, Tanjungsari, and Garut, experiences logistics inefficiencies that cause substantial expenses and less than optimal routing. Using two popular Vehicle Routing Problem (VRP) methods (the Nearest Neighbor and Saving Matrix), this study sets out to minimize transportation costs and travel distance in order to optimize distribution routes. Saving Matrix method builds distance matrix, locates cost-saving prospects by consolidating routes, and assigns deliveries according to vehicle volume. The Nearest Neighbor decreased transportation costs by 65.59% and reduced traveling distance by 1,500 km, according to findings. The Saving Matrix method reduced the cost by 65.62% and the distance travelled by 1,518 km. Both approaches improved logistics efficiency, but the Saving Matrix showed a small advantage. These findings offer data-informed insights to help organizations minimize costs through optimized distribution while providing higher quality service.